An Axiological Study of Wayang Da'wah in the History of the Spread of Islam in Indonesia - Agus Fatuh Widoyo (TATHO: International Journal of Islamic Thought and Sciences, 2026)
The aim of this qualitative study, conducted as a literature review, is to explore the axiological aspects related to the function of wayang dakwah in the history of the spread of Islam on the island of Java (Indonesia). This study employs a content analysis approach. Data were obtained from various academic sources discussing wayang dakwah in the history of the spread of Islam in Indonesia. The findings indicate that, historically, wayang dakwah has been passed down from generation to generation as an integral part of cultural arts, closely linked to religious values within the history of Javanese Muslim society. In practice, wayang dakwah has made a significant contribution to the dissemination of Islamic teachings, encompassing socio-cultural, political, religious, and other aspects. The contribution of this study emphasises that the acculturation between cultural arts and religion can create an effective and accommodating form of artistic media for disseminating religious values within local communities.